Accurate Circuit Parameter Determination of a Resonant Power Frequency Converter for High-Voltage and Partial Discharge Tests - Banyat Leelachariyakul; Peerawut Yutthagowith (My University, 2022)
For high-voltage (HV) and partial discharge (PD) tests on high-voltage equipment, a resonant power frequency converter has recently been developed. A single-phase power frequency converter with a resonant tuning and filter circuit and an HV testing transformer comprise the developed system. A difficulty in the tuning and filter circuit design is the unknown testing system circuit parameters, including unknown parasitic inductance, capacitance, and internal resistance. In this paper, a system with a voltage rating of 75 kVrms, apparent power of 40 kVA, and an operating frequency from 50 Hz to 200 Hz is considered for determination of the equivalent circuit parameters. From the determined circuit parameters, the appropriate resonant tuning and filter circuit was designed effectively. The transfer functions of the input and output testing voltages, along with the transfer impedance of the input voltage and signal voltage of the PD measuring port, were analyzed. The system design was verified by experiments with a voltage transformer. The gain of the transfer impedance was about 15 and 4 at the testing frequencies of 50 Hz and 200 Hz, respectively. With the proper design, it is possible to generate an output voltage waveform that is almost entirely sinusoidal and has a background noise level of under 1 pC. According to the experimental results, the system design of the resonant converter and the method for determining the equivalent circuit are very helpful for the HV and PD tests of voltage transformers in actual practice.
Keywords: LC circuit; Advanced DC-DC Converters